Video-assisted thoracic surgery for thymoma: long-term follow-up results and prognostic factors—single-center experience of 150 cases - Li, Jian-Feng; Hui, Ben-Gang; Li, Xiao; Xiao, Rong-Xin; Jiang, Guan-Chao; Liu, Jun; Wang, Jun (Journal of Thoracic Disease, 2018)
Background: The use of video-assisted thoracic surgery (VATS) in the treatment of thymoma is becoming more and more common. The aim of this study was to evaluate safety and effectiveness of thoracoscopic treatment of thymoma and, more importantly, to report long-term follow-up results of a large single-center cohort. Methods: A retrospective review of a prospective database was performed. In total, 150 patients who underwent VATS resection for thymoma at Peking University People’s Hospital from April 2001 to November 2014 were retrospectively reviewed. Results: Average operation time was 140.1±54.2 min, median blood loss was 50 mL (range, 10–700 mL), median post-operative drainage time was 3 days (range, 1–11 days), and median length of post-op stay was 5 days (range, 2–20 days); 134 patients (89.3%) were followed up successfully. Median follow-up was 59.5 months (range, 2–187 months). Five- and 10-year recurrence free survival (RFS) rates of entire group were 96.5% and 94.4%, respectively; 5- and 10-year RFS rates for Masaoka stages I + II were 98.1% and 98.1%, respectively; 5- and 6-year RFS rates for Masaoka stage III were 90% and 60%, respectively. One case of recurrence in ve Masaoka stage IV patients was observed, and 4-year RFS was 80%. Multivariable analysis indicated that recurrence tended to occur in Masaoka stages III + IV patients (P=0.037, HR =12.69, 95% CI: 1.17–138.22) and older patients had a lower risk of recurrence (P=0.029, HR =0.87, 95% CI: 0.77–0.99). Myasthenia gravis (MG) presented in 44 patients (29.3%), of which 36 patients (81.8%) were followed up. Nine patients achieved complete remission, and 19 patients had symptom improvement after surgery. Overall response rate of MG was 77.8% (28/36). Conclusions: VATS was a safe and effective procedure for treatment of thymomas with satisfactory prognosis. MG with thymoma treated by VATS had comparable neurological outcome to that associated with the trans-sternal approach.